2018
DOI: 10.1152/ajpendo.00057.2018
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-dependent deacetylase SIRT3 in adipocytes is dispensable for maintaining normal adipose tissue mitochondrial function and whole body metabolism

Abstract: Mitochondrial dysfunction in adipose tissue is involved in the pathophysiology of obesity-induced systemic metabolic complications, such as type 2 diabetes, insulin resistance, and dyslipidemia. However, the mechanisms responsible for obesity-induced adipose tissue mitochondrial dysfunction are not clear. The aim of present study was to test the hypothesis that nicotinamide adenine dinucleotide (NAD)-dependent deacetylase sirtuin-3 (SIRT3) in adipocytes plays a critical role in adipose tissue mitochondrial bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 54 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…Data obtained from in vitro studies showed mitochondrial SIRT3 regulates UCP1 and PGC1α expression and oxygen consumption in brown adipocytes (31). However, whole-body Sirt3-deficient mice and adipocyte-specific mitochondrial Sirt3 knockout (AMiSKO) mice have normal BAT function and cold tolerance (32,33), suggesting SIRT3 alone is not a major downstream mediator in vivo. Nonetheless, we cannot exclude the possibility of the functional redundancy of mitochondrial sirtuins (SIRT3-5), which was recently found in retinal cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from in vitro studies showed mitochondrial SIRT3 regulates UCP1 and PGC1α expression and oxygen consumption in brown adipocytes (31). However, whole-body Sirt3-deficient mice and adipocyte-specific mitochondrial Sirt3 knockout (AMiSKO) mice have normal BAT function and cold tolerance (32,33), suggesting SIRT3 alone is not a major downstream mediator in vivo. Nonetheless, we cannot exclude the possibility of the functional redundancy of mitochondrial sirtuins (SIRT3-5), which was recently found in retinal cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation by increased intracellular NAD + levels, SIRT1 and SIRT3 culminate in enhancing energy expenditure and counteracting the weight gain and obesity‐related metabolic abnormalities associated with the ingestion of a lard‐based HFD in mice . Adipose SIRT1 expression improves insulin sensitivity in humans and mice, though the role of SIRT3 on mitochondrial function in adipocytes and whole‐body metabolism remains a controversy . We analyzed gene expression of SIRT1 and SIRT3 in WAT of niacin‐treated mice and found that the HFD based on milk cream was repressive for both genes while HFDs based on olive oil promoted their transcriptional activities, consistent with the selective effects of such HFDs on the levels of adipose NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and diabetes are becoming ever more common around the world and are now trending with younger people. Although a recent study suggests that SIRT3 is dispensable in adipocyte metabolism and obesity-induced metabolic complications 157 , SIRT3 in fact is important in obesity and diabetes. Of note, insulin resistance and vascular dysfunction are common in obese patients, which are exacerbated by SIRT3 deficiency 158 , 159 .…”
Section: Sirt3 and Human Diseasementioning
confidence: 99%